Structure and composition of Au/Co magneto-plasmonic nanoparticles - Bhattarai, Nabraj (2013)
The fabrication of bimetallic magnetic nanoparticles (NPs) smaller than the size of single magnetic domain is very challenging because of the agglomeration, non-uniform size, and possible complex chemistry at nanoscale. In this paper, we present an alloyed ferromagnetic 4 ± 1 nm thiolated Au/Co magnetic NPs with decahedral and icosahedral shape. The NPs were characterized by Cs-corrected scanning transmission electron microscopy (STEM) and weretheoretically studied by Grand Canonical Monte Carlo simulations. Comparison of Z-contrast imaging and energy dispersive x-ray spectroscopy used jointly with STEM simulated images from theoretical models uniquely showed an inhomogeneous alloying with minor segregation. The magnetic measurements obtained from superconducting quantum interference device magnetometer exhibited ferromagnetic behavior. This magnetic nanoalloy in the range of single domain is fully magnetized and carries significance as a promising candidate for magnetic data recording, permanent magnetization, and biomedical applications.